PENGARUH IKLAN YOUTUBE TERHADAP MINAT BELI VIVO SMARTPHONE (Survei Pada Mahasiswa Universitas Singaperbangsa Karawang Jurusan Manajemen Angkatan 2016, 2017 Dan 2018) - Hanna Arnianti; Gina Khoirunnisa; Hafizh Arzaqi; Geulis Geulis; Herlina Herlina (Cakrawala Management Business Journal, 2019)
The development of media applications has helped improve the way an organization or company advertises. How to advertise is very influential on the company's strategy in choosing the media used for marketing and promotional communications. Electronic advertisements include radio advertisements, television advertisements, film advertisements, internet media advertisements and so on. The media used by Indonesian Internet users is television and YouTube media, the types of advertisements on YouTube videos are streamvideo ads and video ads. Vivo is one company that uses YouTube services as a means of advertising or promotion. Huawei, Oppo and Vivo both experienced a relatively high increase in global sales compared to the previous year, but the lowest sales quantity of some Chinese smartphones was Vivo. This research was conducted with the aim of knowing the effect of YouTube advertising on the interest in buying Vivo Smartphone. This study uses simple regression to determine the effect of YouTube ad variables on buying interest. The results of this study are based on 211 respondents, where the YouTube advertising variable affects buying interest by 59.9%, while the remaining 40.1% is influenced by variables outside the research variable.